Factors affecting life satisfaction among retired older adults - Gu, Minkyung; Yu, Jakyung; Sok, Sohyune (Frontiers in Public Health, 2025)
BackgroundThe population of older adult people is rapidly increasing in South Korea. Consequently, older adult people’s life satisfaction, especially the retired older adult, is emerging as a social issue and not just an individual problem.ObjectiveThis study aimed to examine and identify the factors affecting the life satisfaction of the retired older adult.MethodsA cross-sectional descriptive design was employed. The sample included 149 retired older adults living in Gyeonggi or Seoul, South Korea. The data included the general characteristics of study participants and the level of their life satisfaction, health conservation, self-efficacy, and social activity. The data was collected from January to February 2020 and analyzed using SPSS PC+ version 23.0.ResultsThe factors affecting life satisfaction in retired older adults were health conservation (β = 0.28, p < 0.001), self-efficacy (β = 0.26, p = 0.001), marital status (β = 0.24, p = 0.001), social activity (β = 0.18, p = 0.018), and family relationships (β = −0.15, p = 0.048). The explanatory power of the final regression model was 59%.ConclusionThe study suggests that to improve the life satisfaction of retired older adults, their health conservation, self-efficacy, social activity, and family relationships should be increased, and married status with spouse needs to be considered. Most importantly, health professionals need to pay attention to the factors that improve the life satisfaction of retired older adults in community fields.